The Utilization of the Rule of Law for Economic Development in Developing States: The Case of Egypt from Nasser to Mubarak - Ahmed, Mohamed M. (AUC Knowledge Fountain, 2021)
Neoliberal development proponents argue that the rule of law is essential for achieving economic development. It demands adjusting legislative and legal institutional practices to enforce and protect market operations, and the minimizing of state intervention. The IFIs and the developed states adopted this development approach in dealing with developing states through conditional-based lending. Through attaching structural regulative adjustments and the reformation of juristic institutions as preconditions to their fiscal assistance, the IFIs, influenced by the developed states, were able to impose a system of legal economic governance over the developing economies. Across the different development stages, developing states who did not follow the neoliberal development approach managed to achieve greater economic growth in comparison to those who followed it. This paper analyses the rule of law through the different development phases starting in the 1950s till the 2000s. It assesses their interaction with the different economic development paradigms. It defines the techniques and outcomes of adopting the rule of law by the main development actors, mainly the developed and developing states, the IFIs, and the international economic order. It evaluates the essentiality of the rule of law for achieving economic prosperity as a central neoliberal claim. As a case study, this thesis charts the economic transformation of the Egyptian economy from state-led to market-oriented as an economic adjustment transformation that was supervised by the IFIs. The paper argues that, despite the implementation of the rule of law in Egypt as required by the IFIs, the expected economic development was not achieved. Based on such study, this paper undermines the essentiality of the rule of law for economic development and deems it as a neoliberal instrument for economic governance rather than a prerequisite for development.